An Insight into a Rare Case of Osteoclastic Variant of Anaplastic Thyroid Carcinoma Diagnosed by Fine Needle Aspiration Cytology (FNAC) - Jigna Patel; Rutik Thorat; Trupti Jansari (Medical Research and Its Applications Vol. 2, 2024)
The present study highlights a rare case of an osteoclastic variant of Anaplastic Thyroid Carcinoma diagnosed by Fine Needle Aspiration Cytology (FNAC). Anaplastic thyroid carcinoma (ATC) is a rare, highly malignant thyroid tumor with a dismal prognosis Its usual presentation is in elderly patients as a very rapidly growing mass associated with compressive symptoms like pain, hoarseness of voice, dysphagia and shortness of breath. Three primary patterns in ATC are squamoid, giant cell, and spindle cells, albeit these three subtypes usually coexist. ATC’s osteoclastic giant cell variation is incredibly uncommon and is distinguished by the abundance of multinucleated giant cells that resemble osteoclasts. We are reporting here this unusual variant in a 67-year-old male with a history of progressively increasing midline neck swelling and pulmonary metastasis and left jugular vein thrombosis. Cytologically, many multinucleated osteoclast-like giant cells were seen accompanying the malignant spindle cell component. Making the proper cytological diagnosis of the osteoclastic variant of ATC is helpful in determining the proper treatment mortality for these patients.